2019
DOI: 10.1021/acsami.9b13933
|View full text |Cite
|
Sign up to set email alerts
|

Infrared-Radiation-Enhanced Nanofiber Membrane for Sky Radiative Cooling of the Human Body

Abstract: Extreme heat events are mainly responsible for weather-related human mortality due to climate change. However, there is a lack of outdoor thermal management for protecting people from extreme heat events. We present a novel infrared-radiation-enhanced nanofiber membrane (NFM) that has good infrared resonance absorption and selectively radiates thermal radiation of the human body through the atmosphere and into the cold outer space. The NFM comprises polyamide 6 (PA6) nanofibers and randomly distributed SiO2 su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
77
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(77 citation statements)
references
References 32 publications
0
77
0
Order By: Relevance
“…More importantly, the phonon‐polariton resonances of dielectric microspheres with 8 µm diameter lead to a strong emissivity in the mid‐infrared ray (MIR). Wang and co‐workers [ 36 ] designed SiO 2 spheres with sub‐micrometer sizes and random distributions into polyamide 6 nanofibers, enabling a high mid‐IR emittance and enhancing radiative cooling performance. It was revealed that cooling materials possess air permeability and thermal‐moisture comfortability.…”
Section: Development Of Advanced Pdrc Devicesmentioning
confidence: 99%
“…More importantly, the phonon‐polariton resonances of dielectric microspheres with 8 µm diameter lead to a strong emissivity in the mid‐infrared ray (MIR). Wang and co‐workers [ 36 ] designed SiO 2 spheres with sub‐micrometer sizes and random distributions into polyamide 6 nanofibers, enabling a high mid‐IR emittance and enhancing radiative cooling performance. It was revealed that cooling materials possess air permeability and thermal‐moisture comfortability.…”
Section: Development Of Advanced Pdrc Devicesmentioning
confidence: 99%
“…Cellulose is an abundant forest-based material with attractive sustainable properties such as biodegradability, biocompatibility and nontoxicity. This makes cellulose-based materials suitable also for passive radiative cooling in human body applications (Wei et al 2020;Zhang et al 2019;Peng et al 2018;Xiao et al 2019). Furthermore, the visible properties of cellulose materials can be manipulated by additives or via changes in the structural arrangement at the nanoscale and microscale (Vasileva et al 2017;Koivurova et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced with permission. [ 103 ] Copyright 2019, American Chemical Society. Reproduced with permission.…”
Section: Fundamental Principles For Radiative Coolingmentioning
confidence: 99%